2021
DOI: 10.3390/jpm11020077
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Extracellular Vesicle Characteristics Correlate with Tumor Differentiation and Predict Overall Survival in Patients with Pancreatic Ductal Adenocarcinoma Undergoing Surgery with Curative Intent

Abstract: Better preoperative characterization of patients with pancreatic ductal adenocarcinoma (PDAC) would aid in treatment optimization. Extracellular vesicles (EV) are promising, largely unexplored biomarkers in PDAC. This study aimed to evaluate if plasma EV characteristics are associated with PDAC clinical characteristics and overall survival (OS). The prospective cohort included 34 PDAC patients undergoing surgery with curative intent. Patient data and plasma samples were collected preoperatively, intraoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Compared to healthy control (Figures 5 and S12), PDAC patients had (1) smaller CD9-enriched EVs; (2) larger and rounder IGF1R-enriched EVs with more tetraspanin molecules. Interestingly, recent data (Badovinac et al, 2021) indicates that PDAC patients with poorly differentiated resectable tumours had significantly larger plasma EVs. This suggests that the biogenesis or clearance of these EV populations may be affected.…”
Section:  Discussionmentioning
confidence: 99%
“…Compared to healthy control (Figures 5 and S12), PDAC patients had (1) smaller CD9-enriched EVs; (2) larger and rounder IGF1R-enriched EVs with more tetraspanin molecules. Interestingly, recent data (Badovinac et al, 2021) indicates that PDAC patients with poorly differentiated resectable tumours had significantly larger plasma EVs. This suggests that the biogenesis or clearance of these EV populations may be affected.…”
Section:  Discussionmentioning
confidence: 99%
“…As well as such changes in their molecular composition in blood, the EV concentrations and size profile might be linked to physiological factors like hypoxia, autophagy or stress, and hence be typical for a diverse set of diseases ( Vasconcelos et al, 2019 ). Indeed, increases in plasma EV levels have been reported in connection with several cancers ( Navarro et al, 2019 ; Badovinac et al, 2021 ), and also for cardiovascular and autoimmune diseases ( Dickhout and Koenen, 2018 ; Maione et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…EV based serum diagnostics provides an additional and powerful diagnostic component in the field of liquid biopsies (Yee et al, 2020). With regard to EV diagnostic in PDAC, the concentration and size of EVs in patient serum has been correlated with tumor differentiation and overall survival in PDAC patients (Badovinac et al, 2021), but no specific cargo analysis of "diagnostic" EVs in serum has been reported up to now. In this respect, our results provide some novelties: First of all, we identified ADAM8, a protease with a therapeutic potential in PDAC, to be located in EVs that meet all criteria for exosomes.…”
Section: Discussionmentioning
confidence: 99%